Magnetic switching of nanoscale antidot lattices - Wiedwald, Ulf; Gräfe, Joachim; Lebecki, Kristof M.; Skripnik, Maxim; Haering, Felix; Schütz, Gisela; Ziemann, Paul; Goering, Eberhard; Nowak, Ulrich (Beilstein Journal of Nanotechnology, 2016)
We investigate the rich magnetic switching properties of nanoscale antidot lattices in the 200 nm regime. In-plane magnetized Fe, Co, and Permalloy (Py) as well as out-of-plane magnetized GdFe antidot films are prepared by a modified nanosphere lithography allowing for non-close packed voids in a magnetic film. We present a magnetometry protocol based on magneto-optical Kerr microscopy elucidating the switching modes using first-order reversal curves. The combination of various magnetometry and magnetic microscopy techniques as well as micromagnetic simulations delivers a thorough understanding of the switching modes. While part of the investigations has been published before, we summarize these results and add significant new insights in the magnetism of exchange-coupled antidot lattices.
Keywords: antidot lattice; first-order reversal curves; Kerr microscopy; magnetic nanostructures; magnetic switching; micromagnetic simulations; plasma etching; spin ice; X-ray microscopy

(untitled) - Braun, J.; Gompf, B.; Kobiela, G.; Dressel, M. (Phys. Rev. Lett., 2009)

(untitled) - Papaioannou, E. T.; Kapaklis, V.; Patoka, P.; Giersig, M.; Fumagalli, P.; Garcia-Martin, A.; Ferreiro-Vila, E.; Ctistis, G. (Phys. Rev. B, 2010)

(untitled) - Kern, K.; Heitmann, D.; Grambow, P.; Zhang, Y. H.; Ploog, K. (Phys. Rev. Lett., 1991)

(untitled) - Weiss, D.; Richter, K.; Menschig, A.; Bergmann, R.; Schweizer, H.; von Klitzing, K.; Weimann, G. (Phys. Rev. Lett., 1993)

(untitled) - Wördenweber, R.; Dymashevski, P.; Misko, V. R. (Phys. Rev. B, 2004)

(untitled) - Eisenmenger, J.; Oettinger, M.; Pfahler, C.; Plettl, A.; Walther, P.; Ziemann, P. (Phys. Rev. B, 2007)

(untitled) - Wang, C. C.; Adeyeye, A. O.; Singh, N. (Nanotechnology, 2006)

(untitled) - Cumings, J.; Heyderman, L. J.; Marrows, C. H.; Stamps, R. L. (New J. Phys., 2014)

(untitled) - Schumann, A.; Sothmann, B.; Szary, P.; Zabel, H. (Appl. Phys. Lett., 2010)

(untitled) - Castán-Guerrero, C.; Bartolomé, J.; Bartolomé, F.; Garcia, L. M.; Sesé, J.; Strichovanec, P.; Herrero-Albillos, J.; Merazzo, K. J.; Vázquez, M.; Vavassori, P. (J. Korean Phys. Soc., 2013)

(untitled) - Fischer, U. C.; Zingsheim, H. P. (J. Vac. Sci. Technol. (N. Y., NY, U. S.), 1981)

(untitled) - Plettl, A.; Enderle, F.; Saitner, M.; Manzke, A.; Pfahler, C.; Wiedemann, S.; Ziemann, P. (Adv. Funct. Mater., 2009)

(untitled) - Wang, C. C.; Adeyeye, A. O.; Wu, Y. H. (J. Appl. Phys., 2003)

(untitled) - Wiedwald, U.; Haering, F.; Nau, S.; Schulze, C.; Schletter, H.; Makarov, D.; Plettl, A.; Kuepper, K.; Albrecht, M.; Boneberg, J.; Ziemann, P. (Beilstein J. Nanotechnol., 2012)

(untitled) - Streubel, R.; Kronast, F.; Rößler, U. K.; Schmidt, O. G.; Makarov, D. (Phys. Rev. B, 2015)

(untitled) - Haering, F.; Wiedwald, U.; Häberle, T.; Han, L. Y.; Plettl, A.; Koslowski, B.; Ziemann, P. (Nanotechnology, 2013)

(untitled) - Mengotti, E.; Heyderman, L. J.; Rodríguez, A. F.; Nolting, F.; Hügli, R. V.; Braun, H.-B. (Nat. Phys., 2011)

(untitled) - Lenk, B.; Ulrichs, H.; Garbs, F.; Münzenberg, M. (Phys. Rep., 2011)

(untitled) - Neusser, S.; Grundler, D. (Adv. Mater., 2009)

(untitled) - Wiedemann, S.; Plettl, A.; Walther, P.; Ziemann, P. (Langmuir, 2013)

(untitled) - Preisach, F. (Z. Phys., 1935)

(untitled) - Mayergoyz, I. D. (Phys. Rev. Lett., 1986)

(untitled) - Gräfe, J.; Schmidt, M.; Audehm, P.; Schütz, G.; Goering, E. (Rev. Sci. Instrum., 2014)

OOMMF User's Guide - Donahue, M. J.; Porter, D. G. (National Institute of Standards and Technology, 1999)

(untitled) - Kazantseva, N.; Hinzke, D.; Nowak, U.; Chantrell, R. W.; Atxitia, U.; Chubykalo-Fesenko, O. (Phys. Rev. B, 2008)

Handbook of Magnetism and Advanced Magnetic Materials - Miltat, J.; Donahue, M. J. (Numerical Micromagnetics : Finite Difference Methods, 2007)

Introduction to the Theory of Ferromagnetism - Aharoni, A. (Oxford University Press, 2000)

(untitled) - Lebecki, K. M.; Hinzke, D.; Nowak, U.; Chubykalo-Fesenko, O. (Phys. Rev. B, 2012)

(untitled) - Haering, F.; Wiedwald, U.; Nothelfer, S.; Koslowski, B.; Ziemann, P.; Lechner, L.; Wallucks, A.; Lebecki, K.; Nowak, U.; Gräfe, J.; Goering, E.; Schütz, G. (Nanotechnology, 2013)

http://idc2d.sourceforge.net

(untitled) - Evans, R. F. L.; Hinzke, D.; Atxitia, U.; Nowak, U.; Chantrell, R. W.; Chubykalo-Fesenko, O. (Phys. Rev. B, 2012)

http://www.ctcms.nist.gov/~rdm/mumag.org.html

Dynamic Response of the Magnetisation to Picosecond Heat Pulses - Kazantseva, N. (University of York, 2008)

(untitled) - Lyberatos, A.; Guslienko, K. Yu (J. Appl. Phys., 2003)

(untitled) - Krupa, M.; Korostil, A. (Int. J. Phys., 2013)

(untitled) - Vahaplar, K.; Kalashnikova, A. M.; Kimel, A. V.; Gerlach, S.; Hinzke, D.; Nowak, U.; Chantrell, R.; Tsukamoto, A.; Itoh, A.; Kirilyuk, A.; Rasing, T. (Phys. Rev. B, 2012)

(untitled) - Paz, E.; Cebollada, F.; Palomares, F. J.; González, J. M.; Im, M.-Y.; Fischer, P. (J. Appl. Phys., 2012)

(untitled) - Ruiz-Feal, I.; Lopez-Diaz, L.; Hirohata, A.; Rothman, J.; Guertler, C. M.; Bland, J. A. C.; Garcia, L. M.; Torres, J. M.; Bartolome, J.; Bartolome, F.; Natali, M.; Decanini, D.; et al. (J. Magn. Magn. Mater., 2002)

(untitled) - Smyth, J. F.; Schultz, S.; Fredkin, D. R.; Kern, D. P.; Rishton, S. A.; Schmid, H.; Cali, M.; Koehler, T. R. (J. Appl. Phys., 1991)

Tuning the magnetic properties of thin films by interaction with perodic nanostructures - Haering, F. (University of Ulm, 2013)

(untitled) - Paul, D. I. (J. Appl. Phys., 1982)

(untitled) - Kläui, M.; Ehrke, H.; Rüdiger, U.; Kasama, T.; Dunin-Borkowski, R. E.; Backes, D.; Heyderman, L. J.; Vaz, C. A. F.; Bland, J. A. C.; Faini, G.; Cambril, E.; Wernsdorfer, W. (Appl. Phys. Lett., 2005)

(untitled) - Castelnovo, C.; Moessner, R.; Sondhi, S. L. (Nature, 2008)

(untitled) - Ladak, S.; Read, D. E.; Perkins, G. K.; Cohen, L. F.; Branford, W. R. (Nat. Phys., 2010)

(untitled) - Ladak, S.; Read, D. E.; Branford, W. R.; Cohen, L. F. (New J. Phys., 2011)

(untitled) - Tanaka, M.; Saitoh, E.; Miyajima, H.; Yamaoka, T.; Iye, Y. (Phys. Rev. B, 2006)

(untitled) - Ladak, S.; Walton, S. K.; Zeissler, K.; Tyliszczak, T.; Read, D. E.; Branford, W. R.; Cohen, L. F. (New J. Phys., 2012)

(untitled) - Branford, W. R.; Ladak, S.; Read, D. E.; Zeissler, K.; Cohen, L. F. (Science, 2012)

(untitled) - Ladak, S.; Read, D.; Tyliszczak, T.; Branford, W. R.; Cohen, L. F. (New J. Phys., 2011)

(untitled) - Farhan, A.; Derlet, P. M.; Kleibert, A.; Balan, A.; Chopdekar, R. V.; Wyss, M.; Perron, J.; Scholl, A.; Nolting, F.; Heyderman, L. J. (Phys. Rev. Lett., 2013)

(untitled) - Wang, C. C.; Adeyeye, A. O.; Singh, N.; Huang, Y. S.; Wu, Y. H. (Phys. Rev. B, 2005)

(untitled) - Meng, T.-J.; Lalöe, J.-B.; Holmes, S. N.; Husmann, A.; Jones, G. A. C. (J. Appl. Phys., 2009)

(untitled) - Ctistis, G.; Papaioannou, E.; Patoka, P.; Gutek, J.; Fumagalli, P.; Giersig, M. (Nano Lett., 2009)

(untitled) - Béron, F.; Pirota, K. R.; Vega, V.; Prida, V. M.; Fernández, A.; Hernando, B.; Knobel, M. (New J. Phys., 2011)

(untitled) - Manzin, A.; Bottauscio, O. (J. Phys. D: Appl. Phys., 2012)

(untitled) - Gräfe, J.; Haering, F.; Tietze, T.; Audehm, P.; Weigand, M.; Wiedwald, U.; Ziemann, P.; Gawroński, P.; Schütz, G.; Goering, E. J. (Nanotechnology, 2015)

(untitled) - Amaladass, E.; Ludescher, B.; Schütz, G.; Tyliszczak, T.; Eimüller, T. (Appl. Phys. Lett., 2007)

IEEE Magnetics Conference (INTERMAG) 2015 - Gräfe, J.; Haering, F.; Stahl, K.; Weigand, M.; Skipnik, M.; Nowak, U.; Ziemann, P.; Wiedwald, U.; Schütz, G.; Goering, E. (CG-09, Beijing, China, 11.5.2015-15.5.2015, 2015)

https://www.thermofisher.com

http://silson.com

(untitled) - Suni, T.; Henttinen, K.; Suni, I.; Mäkinen, J. (J. Electrochem. Soc., 2002)

(untitled) - Trautvetter, M.; Wiedwald, U.; Paul, H.; Minkow, A.; Ziemann, P. (Appl. Phys. A, 2011)

(untitled) - Gräfe, J.; Weigand, M.; Träger, N.; Schütz, G.; Goering, E.; Skripnik, M.; Nowak, U.; Haering, F.; Ziemann, P.; Wiedwald, U. (Phys. Rev. B, 2016)